DEVELOPMENT OF VILLAGE PROFILE AS THE VILLAGE DEVELOPMENT PLANNING INPUT IN TARAI BANGUN VILLAGE TAMBANG DISTRICT KAMPAR REGENCY - sulaiman, sulaiman; prihati, prihati; aguswan, aguswan (Jurnal Niara, 2019)
purpose of this study was to determine and analyze the ability of village apparatus in compiling village profiles and utilizing village profiles in village development planning. This research is descriptive analysis with a qualitative approach. The results showed that the profile of Tarai Bangun village had not been arranged accurately, actual and comprehensively because in filling out the village profile it had not fully used the correct data sources and procedures. This is inseparable from the low level of village apparatus capacity and lack of community participation and the lack of budget used in collecting village profile data. Furthermore, in utilizing village profile data which is expected to be used as a baseline with village development actors in supporting planning, organizing, implementing, controlling, evaluating and policies, programs and activities in Tarai Bangun village, it cannot be realized. Another obstacle is the lack of attention of the regional government in collecting village profiles so that the use of village profile data cannot be used as inputs or sources of information in village development planning. Therefore, there is a need for local government policies to improve the knowledge and skills of village officials through the provision of training and training or assistance in filling out village profiles in accordance with the format of the Minister of Home Affairs Regulation No. 12 of 2007.